Influence of feeding weanmor+® to sows on stillborn rate and preweaning mortality - DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 239 sows (PIC C-22) were used in this experiment. Sows were randomly allotted to one of the two experimental treatments approximately 5 days before their expected farrowing date. Control sows did not receive any topdress; sows on the WEANMOR+® treatment received a single daily topdress of 25 g of WEANMOR+®. Topdressing the sow feed with WEANMOR+® reduced (P<0.06) urine pH, but number of total pigs born, mummied, fostered, died, or weaned were not influenced by treatment (P>0.67). There was a parity group-by-stillborn interaction (P<0.10) in which feeding WEANMOR+® reduced the number of stillborn pigs in the parity 2 to 5 sows, with a numeric increase in stillborns when WEANMOR+® was fed to sows that were parity 6 and over.
Swine research, 2005 is known as Swine day, 2005
Keywords: Sows; Litter size; Diet acidification; Swine